Agroecological characteristics of the effect of a mixture of probiotic preparations with concomitant formation water on soil microorganisms - Pysarenko, Pavlo; Samojlik, Maryna; Galytska, Maryna; Tsova, Yuriy; Pischalenko, Maryna (Ecological Questions, 2023)
In the context of energy and environmental crisis, the search for new substances ensuring the formation of microbial cenosis with a rich composition of agronomically valuable groups of bacteria, the optimal level of humification, and the increase of organic matter in the soil will allow to substantiate innovative environmentally safe types of fertilizers and plant protection under specific soil and climatic conditions. Therefore, the aim of the research was to study the peculiarities of the formation and functioning of microbial cenosis of podzolic chernozem soil and the intensity of soil-biological processes upon application of a mixture of probiotic preparations and concomitant formation water in different concentrations. Different concentrations of concomitant formation water (СFW) and probiotic preparations were applied to the soil in the selected plots, and the soil microbial cenoses of farmland were evaluated in the spring and autumn periods on days 15, 30, and 60 after application of the mixtures. Soil without the application of any substances was considered a control variant. The most effective impact is observed on day 30 after application, there is an activation of microbiological processes on day 15, and a significant decrease is observed on day 60, although higher than the control due to the prolonged action of СFW. It was determined that the best variant of the experiment in both spring and autumn periods to improve the viability of soil microbial cenosis is the option of joint use of СFW at a concentration of 900 L ha-1 and probiotic Sviteco-Agrobiotic-01 diluted in a ratio of 1:10 (dose 100 L ha-1). In particular, the total number of all groups of bacteria in the soil increases with the use of probiotics diluted in a ratio of 1:10 (15-31% compared to control) and is the maximum when using a mixture of СFW at a dose of 900 L ha-1 and 10% probiotic (by 82-102% compared to control). Based on the analysis of the coefficients of mineralization-immobilization, oligotrophy, and pedotrophy, it was found that the application of СFW mixture and probiotic increases the soil nutrient content for different ecological and trophic groups of bacteria, reduces the rate of humus decomposition and creates favorable conditions for the development of soil bacteria.